Jordan automorphisms, Jordan derivations of generalized triangular matrix algebra - Aiat Hadj Ahmed Driss (International Journal of Mathematics and Mathematical Sciences, 2005)
We investigate Jordan automorphisms and Jordan derivations of a class of algebras called generalized triangular matrix algebras. We prove that any Jordan automorphism on such an algebra is either an automorphism or an antiautomorphism and any Jordan derivation on such an algebra is a derivation.